Regional development in ireland - problems of goal formulation and objective specification - O' Farrell, PN (Economic & Social Studies, 1970)
The establishment of a consistent set of goals and objectives is fundamental to the planning process since planning is concerned with attempting to realise predetermined results. Although specification of objectives is a component part of all planning on any spatial scale, as well as for the firm, surprisingly little attention has been paid to their identification and formulation. Setting bbjectiyes is especially complex for there are no analytical techniques which permit consistentquantitative correlation and comparison Between the many different elements and qualitative aspects which should be considered. Until such methods are developed, understanding the dynamics of the region must be achieved by partial statistical' sub-systems analysis, logical arguments, experience and continuous observation. Efficient planning at any level requires a clear statement of goals, but a multitude of decisions must be effected in order to reach that stage.
Keywords: Regional Development - Ireland